The Political Geography of Water Provision in Paris, Ontario, 1882–1924 - Hagopian, John (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 1994)
This article examines the social and political factors which influenced the development of the Paris, Ontario waterworks system from 1882 to 1924. Commercial, industrial and upper-class residential areas received prior service, even though the debt financing of the system was borne by taxpayers generally. This pattern reflects the purpose of the system, which was to protect valuable property from fire, rather than to improve public health. Municipal voting laws gave disproportionate power to owners of property and thus allowed their will to prevail. The findings could be expected in all Ontario municipalities, as municipal voting laws were provincially legislated. Historically, there has been a bias in water provision in favour of the affluent.